Synthesis, Transfer, and Gas Separation Characteristics of MOF-Templated Polymer Membranes - Schmitt S. Sophia; Shishatskiy S. Sergey; Krolla P. Peter; An Qi; Begum S. Salma; Welle A. Alexander; Mokhamed Takhid Khashim (Hashem) Abdelrazek (2019, 2019)
Title screen